2017
DOI: 10.4236/jep.2017.83027
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Pond Water and Sediment in Coal Burning Area

Abstract: The pond water is used by a variety of animals i.e. mammals, birds, duck, and fish. Sediments play a significant role in determining the overall environmental quality for the living organism. Therefore, in this work, chemical characterization of pond water and sediment in the largest coal burning basin of India i.e. Korba basin is described. Elements i.e. C, O, S, F, Cl, Na, Mg, Al, Si, P, K, Ca, Ti, Fe, As, Cr, Cu, Zn, Cd, Pb, and Hg were quantified. Toxic metals i.e. As, Cd, Hg, and Pb were highly enriched i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…4 In the particular case of China, Bangladesh and India, values of As content in eld, surface, pond, ground, sewage and industrial waste water have been reported, and ascribed to mineralization of arsenopyrite. [158][159][160]165,167,169,[172][173][174][175][176][177] In African countries, both surface and groundwater are also seriously polluted with arsenic due to industrial activities. 178 Examples for Bostwana, Ethiopia, Ghana, Moroco, Nigeria, South Africa and Tanzania 42,145,146,150,155 are presented in Table 3.…”
Section: Sample Collection Preservation and Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In the particular case of China, Bangladesh and India, values of As content in eld, surface, pond, ground, sewage and industrial waste water have been reported, and ascribed to mineralization of arsenopyrite. [158][159][160]165,167,169,[172][173][174][175][176][177] In African countries, both surface and groundwater are also seriously polluted with arsenic due to industrial activities. 178 Examples for Bostwana, Ethiopia, Ghana, Moroco, Nigeria, South Africa and Tanzania 42,145,146,150,155 are presented in Table 3.…”
Section: Sample Collection Preservation and Pretreatmentmentioning
confidence: 99%
“…Ambagrh tehsil and Korba city, with values up to 256 and 154 mg kg −1 , respectively. Pollution of As in these locations were attributed to arsenopyrite leaching 165 and coal burning and alumina roasting, 167 respectively.…”
Section: Sample Collection Preservation and Pretreatmentmentioning
confidence: 99%
“…The Korba basin in Chhattisgarh, India, characterized by coal mining activities, has witnessed pollution of soil, sediments, and water with F − and heavy metals (Patel 2016(Patel , 2024Sharma et al, 2017Sharma et al, , 2019. As in the Korba basin has long history of coal mining activities, discharge of untreated wastewater, mine drainage and water runoff are the primary sources of pollution into nearby surface water bodies (Patel 2016(Patel , 2024Sharma et al, 2017Sharma et al, , 2019. However, organic and inorganic carbon in the surface water in coal mine areas is crucial due to thermal plant and coal mining effluents.…”
Section: Introductionmentioning
confidence: 99%
“…The type and location of chemicals thrown into water determine the repercussions (urban areas are highly polluted). Pollutants like lead and cadmium are eaten by minor species [7,8]. Recently, a lot of attention has been paid to creating polluted water treatment systems that are more efficient, less expensive, and long-lasting while also not risking human health or the environment, to develop alternative and cost-effective water and wastewater technologies to remove various sources of pollutants from water [9] .…”
Section: Introductionmentioning
confidence: 99%